Faktor-Faktor yang Berpengaruh pada Waktu Tunggu Pasien dalam Masa Pandemik Covid 19 di Unit Rawat Jalan Rumah Sakit - Ronald Josef Reinhart Walakandou; Gustaaf Alfrits Elisa Ratag; Grace Esther Caroline Korompis (Indonesian Journal of Public Health and Community Medicine, 2021)
Background: Patient waiting time is one element of patient assessment of the quality of a medical service. Waiting time can be in the form of time spent by patients, both before registering, receiving health services, until the process of taking drugs at the pharmacy. The purpose of this study is to analyze the factors that influence the waiting time during the current COVID-19 pandemic. Methods: This is a qualitative research with a case study approach. This research was conducted in July-September 2020 at the Outpatient Unit of the Bhayangkara Hospital, Manado. There were 7 informants in this study. Informants were selected using the snowball method. The variables studied were administration, medical records, human resources (HR), and hospital infrastructure. Data were obtained through in-depth interviews and field observations. Interviews were recorded and made into transcripts and then analyzed using the content analysis method. Results: The results showed that the waiting time for patients in the outpatient unit of the Bhayangkara Manado Hospital during the Covid-19 pandemic is on average in accordance with the hospital's minimum service standard, which is less than 60 minutes. The administrative factor associated with the Covid-19 pandemic situation does not have a negative influence on patient waiting time, where in this pandemic condition, the administrative process actually becomes faster due to the decrease in patients. Factors of medical records, human resources and infrastructure associated with the Covid-19 pandemic situation cause waiting times to be longer. Conclusion: That can be conclude that the waiting time for the outpatient unit at Bhayangkara Hospital Manado is still in accordance with the minimum service standards of the hospital where the influencing factors are administrative, human resources, medical records and hospital infrastructure factors.